Model of Community Health Nursing Care to Accelerate MDGs on Health Sanitation Behavior Sector - Martono, Martono; Satino, Satino (Universitas Airlangga, 2015)
Introduction: Health promotion have an important role in order to improve communityâs independency on health and healthy lifestyle which influenced by socio-cultural around them. The purpose of this study was to examine the contribution of health volunteer activeness, family empowerment, and healthy lifestyle perception on health sanitation behavior sector, so that can help to accelerate MDGs acheivement. Method: This was explanatory research with cross sectional approach. Ninety nine people were recruited as research samples. Independent variables were health volunteerâs activeness, family empowerment, and health lifestyle perception. While, the dependent variable was health sanitation behavior. Data were collected by using questionnaire. Data were then analyzed by using regression technique. Result: Result had showed that together health volunteerâs activeness, family empowerment, and healthy lifestyle perception have positive contribution to health sanitation behavior (25.4%). While partially, health volunteerâs activeness has result (0.2%), family empowerment (15.3%), and healthy lifestyle perception (9.9%). Discussion: The successfullness of health sanitation on community needs participation from family and community itself. Community health nurses should conduct health promotion as an effort to improve communityâs knowledge about health behavior.Keywords: posdaya, health volunteerâs activeness, family empowerment, and healthy lifestyle perception